Developing digital currency from an Islamic perspective : the case of blockchain technology - Alzubaidi, Ibrahim Bassam Ibrahim (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Numerous studies ranging from concept papers and reviews were conducted on the matter of blockchain and digital currencies. However, those two areas are not well researched due to its being a new area of research. Furthermore, the research on blockchain applications in the Islamic financial system precisely the potential of digital currency in providing a better alternative to current fiat money system which will be the scope of this research paper. This paper aims to identify the advantages and challenges of developing a digital currency from an Islamic perspective. It includes a background and brief history on the functions of money and the issues associated with fiat monetary system. the study will include an analysis of gold performance to study the elements that defines a money in Islam and compare it with the current concepts of digital currencies to provide better understanding on the concepts that needs to be developed or modified to ensure compliance with Shari'ah. The methodology used in this paper included a library research and a study of current cases to explore the viability of presenting an Islamic digital currency. the finding showed that it is possible to produce a Shari'ah compliant digital currency once all the issues were addressed and presented several cases that tried to solve those issues and provided concepts similar to the objectives of this research.